1980
DOI: 10.1177/014860718000400411
|View full text |Cite
|
Sign up to set email alerts
|

Daily Dressing Change Effects on Skin Flora Beneath Subclavian Catheter Dressings During Total Parenteral Nutrition

Abstract: Septicemia is a persistent problem during total parenteral nutrition (TPN). The skin around the catheter insertion site is one possible source of this infection. In previous studies we showed mechanical cleansing of the skin was more important than the ointment applied; however, alternate day dressing changes did not completely eradicate all skin organisms. The present study was designated to examine the effects of daily dressing changes on the skin flora beneath the subclavian dressing. Fifteen patients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Prompt diagnosis and management of infection and removal of catheters infected with organisms deemed to be difficult to treat by antimicrobial administration alone, such as in fungal infections, may also reduce complications associated with central venous catheter usage. [24][25][26][27][28] Furthermore, our group showed a significant association between higher mean blood glucose levels during hospitalization and increased risk for posthospital BSI in adults on HPN (unpublished study). The purpose of this study was to assess the incidence, manifestations, and etiology of CA-BSI in children receiving HPN in a major metropolitan area of the southeastern United States.…”
Section: Introductionmentioning
confidence: 75%
“…Prompt diagnosis and management of infection and removal of catheters infected with organisms deemed to be difficult to treat by antimicrobial administration alone, such as in fungal infections, may also reduce complications associated with central venous catheter usage. [24][25][26][27][28] Furthermore, our group showed a significant association between higher mean blood glucose levels during hospitalization and increased risk for posthospital BSI in adults on HPN (unpublished study). The purpose of this study was to assess the incidence, manifestations, and etiology of CA-BSI in children receiving HPN in a major metropolitan area of the southeastern United States.…”
Section: Introductionmentioning
confidence: 75%
“…Prominence has been given in the literatureto the hypothesis that infecting organisms in catheter related sepsis come from the skin around the site of entry. Some studies have shown a correlation between positive skin cultures and development of line sepsis ( I I) but others have not demonstrated such a link (4). If our types of dressing were somehow altering skin colonisation around the catheter insertion area, one would have first to be convinced that this was of prime importance in the aetiology of line sepsis to then accept it as an explanation for the marked difference in sepsis rate we observed.…”
Section: Discussionmentioning
confidence: 81%
“…The authors noted, however, that daily changes were costly in terms of labor and supplies and might best be reserved for patients at high risk for sepsis. In contrast to the findings of Jarrard et al (1980), other investigators have observed little relationship between skin flora and catheter sepsis (e.g., Sitges-Serra et al, 1984). These disparate fmdings require further investigation.…”
Section: Enteral Feedingmentioning
confidence: 71%